1980
DOI: 10.1073/pnas.77.5.2782
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epidermal growth factor-urogastrone and its receptor during fetal mouse development

Abstract: Using both a radioimmunoassay and a radioreceptor assay, we have estimated the content of mouse epidermal growth factor-urogastrone (EGF-URO) in fetal mice at 111/2 to 171/2 days of gestation. Concurrently, the amount of specific EGF-URO receptor binding was determined in crude membrane fractions from the embryos. EGF-URO receptor binding is readily detected in membranes from the youngest embryos (day 11/2) and rises steadily up to parturition (18 days); the rise is more marked in embryo membranes derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
53
1
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(61 citation statements)
references
References 15 publications
6
53
1
1
Order By: Relevance
“…Viewed in this light, the abnormal expression of TGFa in the transformed state is analogous to the abnormal expression of developmentally regulated onjogenes (16). Although the appearance of TGFa transcripts in embryos does not necessarily imply that these transcripts are translated to produce TGFa polypeptide, our results are consistent with the earlier observation of Nexo et al (14) that fetal mice at 11 days of gestation contained material that was capable of binding the EGF receptor but was not recognized in an EGF radioimmunoassay. Subsequently, Twardzik et al (18) showed that growth factors with some of the characteristic properties of TGFa could be isolated from 12-to 13-day-old mouse embryos.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Viewed in this light, the abnormal expression of TGFa in the transformed state is analogous to the abnormal expression of developmentally regulated onjogenes (16). Although the appearance of TGFa transcripts in embryos does not necessarily imply that these transcripts are translated to produce TGFa polypeptide, our results are consistent with the earlier observation of Nexo et al (14) that fetal mice at 11 days of gestation contained material that was capable of binding the EGF receptor but was not recognized in an EGF radioimmunoassay. Subsequently, Twardzik et al (18) showed that growth factors with some of the characteristic properties of TGFa could be isolated from 12-to 13-day-old mouse embryos.…”
supporting
confidence: 83%
“…Interestingly Nexo et al (14) found a significant rise in immunoreactive mouse EGF between days 15 and 17. This is approximately the time when in rat gestation the levels of TGFa mRNA have declined.…”
mentioning
confidence: 99%
“…In accordance with these effects, EGF and its receptors are present in various tissues in the fetus and adult (1, 4, 1 1, 14,30,33). Though EGF most probably has an important physiological role, this remains undefined.…”
mentioning
confidence: 99%
“…Boh EGF and its receptor continue to be widely expressed in the embryonic mouse (Nexo et al, 1980;Adamson and Meek, 19841, while particular attention has been focused on its role in the development of the teeth and palate (Partanen, 1990). The role of EGF and TGF 01 in development is, putatively, to contribute to epithelial development in many developing epithelial mesenchymal organs.…”
Section: Mammalsmentioning
confidence: 99%
“…response Nielsen et al (1991) "I-EGF binding Nexo et al (1980) Blastocoel protein Dardik et al (1993) …”
Section: Mammalsmentioning
confidence: 99%